2019
DOI: 10.5114/dr.2019.86906
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy and photochemotherapy in dermatology. Recommendations of the Polish Dermatological Society

Abstract: Light is a component of the electromagnetic waves. The electromagnetic wave consists of mutually inducible electrical and magnetic components that generate variable electric field. This then turns into magnetic field, causing alternating current to flow. Electromagnetic waves include radio waves, microwaves, infrared light, visible light, ultraviolet light, X-rays and gamma radiation. The length of these waves determines their properties. An increase in wavelength is accompanied by a decrease in its radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 37 publications
0
18
0
5
Order By: Relevance
“…W terapii łuszczycy u dzieci wykorzystuje się obecnie naświetlania promieniami o długości 311-313 nm (tzw. narrow-band UVB -NB-UVB) oraz UVA (315-400 nm) w połączeniu z miejscową lub doustną aplikacją psoralenów (PUVA) [1,2]. W większości przypadków fototerapia stosowana jest w skojarzeniu z leczeniem miejscowym.…”
Section: Fototerapiaunclassified
See 3 more Smart Citations
“…W terapii łuszczycy u dzieci wykorzystuje się obecnie naświetlania promieniami o długości 311-313 nm (tzw. narrow-band UVB -NB-UVB) oraz UVA (315-400 nm) w połączeniu z miejscową lub doustną aplikacją psoralenów (PUVA) [1,2]. W większości przypadków fototerapia stosowana jest w skojarzeniu z leczeniem miejscowym.…”
Section: Fototerapiaunclassified
“…Choć u chorych dorosłych przed rozpoczęciem fototerapii rekomenduje się ustalenie minimalnej dawki rumieniowej, to u dzieci proponuje się, aby dawkę początkową ustalać przede wszystkim na podstawie fototypu skóry [1]. W dniach naświetlań pacjent nie powinien dodatkowo eksponować skóry na światło słoneczne.…”
Section: Nb-uvbunclassified
See 2 more Smart Citations
“…Jury et al in their retrospective trial on 25 children with AD showed almost total reduction of lesions in 17 patients [23]. NB-UVB is a recommended therapeutic option in pregnancy [24].…”
Section: Nb-uvbmentioning
confidence: 99%